Interpretación de pruebas genéticas y biomarcadores en la distrofia muscular de Duchenne. - Rivera-Nieto, Carolina; Suárez-Obando, Fernando; Barajas-Viracachá, Norma Carolina; Becerra-Ortiz, Paulo César; Bobadilla-Quesada, Edna Julieth; Bolaños-Almeida, Carlos Ernesto; Cañón-Zambrano, José Manuel; Castellar-Leones, Sandra Milena; Huertas-Quiñones, Manuel; Jurado-Hernández, Jenny Libeth; Lasprilla-Tovar, Juan David; Laza-Gutiérrez, Nicolás J.; et al. (Revista Ciencias de la Salud)
Among the main characteristics of Duchenne muscular dystrophy (DMD) are the damage of muscle fibers during contraction, subsequent chronic muscle damage, inflammation, and subsequent replacement of muscle fibers by fibrous tissue. Biomarkers of the disease can reflect these types of alterations. Biomarkers in dmd are helpful for diagnosis, follow-up, and evaluation of the response to treatment. The indication for requesting different biomarkers varies according to the age and natural history of the disease, and their correct use allows for an adequate therapeutic approach, correct follow-up, and successful rehabilitation. The present review describes the different types of biomarkers and diagnostic methods used in patients with DMD and recommends their appropriate use according to their age and natural history of the disease.